Detection and identification of mutagens and carcinogens as their adducts with guanosine derivatives. - Kasai, H (1984)
For use in screening for environmental mutagens and carcinogens, a highly fluorescent derivative of guanosine, 2'-deoxy-2'-(2",3"-dihydro-2",4"-diphenyl-2"-hydroxy-3"-oxo-1"-pyrrol yl) guanosine (FG), was synthesized. When incubated with FG in aqueous solution, mutagens form adducts that can be analyzed with an HPLC-fluorescence detector-system. By this method, mutagens such as glyoxal, methylglyoxal, 2-(2-furyl)-3-(5-nitrofuryl) acrylamide and 4-nitroquinoline-N-oxide, used as model compounds, were detected rapidly with high sensitivity. Reaction with isopropylideneguanosine (IPG), followed by isolation and characterization of the mutagen-IPG-adduct was found to be a useful method for identifying unknown mutagens in crude samples. This method was successfully applied in identification of the mutagens in heated glucose (200 degrees C, 20 min); glyoxal-IPG and 8-hydroxy-IPG were identified in the reaction mixture.